Examining the psychometric properties of the Schutte’s Self Report Emotional Intelligences Scale (SREIS) - Nurul-Azza Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Emotional intelligence is usually used in order to measure an individual’s effectiveness. One of the instruments that is used to measure emotional intelligence is Schutte’s Self-Report Emotional Intelligence Survey (SREIS). The main objective of this study is to evaluate the psychometric properties of SREIS. A set of SREIS was distributed to 152 undergraduate psychology students from a public university in Malaysia. Other than SREIS, Life Satisfaction Scale (LSS) by Krapu (2006) was also used in this study. In evaluating reliability, Cronbach’s alpha was used, and criterion and construct validity methods were used to test its validity. Results obtained showed that Schutte’s SREIS was valid to be used in Malaysia and using principle component analysis, six components were extracted with 49% variance. The SREIS also showed good criterion validity from the significant correlations with the Life Satisfaction Scale. In addition to that, the results of reliability were satisfactory with Cronbach’s alpha ranging from 0.55 to 0.85 for all the dimensions.